2009
DOI: 10.1590/s1516-14392009000100003
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus mutans attachment on a cast titanium surface

Abstract: This study examined by means of scanning electron microscopy (SEM), the attachment of Streptococcus mutans and the corrosion of cast commercially pure titanium, used in dental dentures. The sample discs were cast in commercially pure titanium using the vacuum-pressure machine (Rematitan System). The surfaces of each metal were ground and polished with sandpaper (#300-4000) and alumina paste (0.3 μm). The roughness of the surface (Ra) was measured using the Surfcorder rugosimeter SE 1700. Four coupons were inse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The colony forming unit (CFU) [12] was used to measure the number of colonies to estimate the number of accumulated bacteria. The variation factors for the inhibition or adhesion characteristics of bacteria are mainly the surface characteristics of the implant, including surface roughness [13][14][15][16], contact angle [17,18], and oxygen content [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The colony forming unit (CFU) [12] was used to measure the number of colonies to estimate the number of accumulated bacteria. The variation factors for the inhibition or adhesion characteristics of bacteria are mainly the surface characteristics of the implant, including surface roughness [13][14][15][16], contact angle [17,18], and oxygen content [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Sterile BHI broth and SDB were renewed at an interval of 3 days for 30 days, and OD was evaluated before media were replaced. Afterward, the specimens were removed from the culture medium …”
Section: Methodsmentioning
confidence: 99%
“…Aykent et al 21 observed a positive correlation between surface roughness and S. mutans adhesion. Several studies shown the oral bacterial adherence on rough surfaces of dental implant biomaterials 22,23 . The concern with the implant surface that comes in contact with the host tissue is with the osseointegration, and nevertheless there are no studies on bacterial adhesion and his effects on titanium surface modified by Nd:YAG laser process.…”
Section: A B Cmentioning
confidence: 99%